Strokovna stališča Slovenskega združenja za reproduktivno medicino (SZRM) o menopavzni medicini - Franić, Damir (Zdravniški vestnik, 2024)
Management of women in menopause and beyond has significantly changed in the new millennium. Randomized clinical trials have remarkably affected indications for hormonal treatment (HT), therefore posing a great challenge to the menopausal society. However, the most recent knowledge confirms that the benefits still outweigh the risks when HT is selected and used correctly. Therefore, we prepared the updated position statement on menopausal medicine, which is in line with current international recommendations and adjusted to Slovenian circumstances.
Keywords: endometriosis; endometrioza; estrogen; menopavza; meopause; progestogen